2018
DOI: 10.1111/ceo.13154
|View full text |Cite
|
Sign up to set email alerts
|

Diet soft drink is associated with increased odds of proliferative diabetic retinopathy

Abstract: Importance: While consumption of soft drink may increase the risk of cardiovascular disease, the relationship between soft drink consumption and diabetes complications is unknown.Background: To explore the association between regular and diet soft drink consumption, and diabetic retinopathy (DR) and diabetic macular oedema (DME).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…The reverse holds for non-caloric flavor consumption (associated with obesity only). Our findings are in line with a previous study conducted among 609 patients with diabetes 14 and found a two-fold increase in proliferative DR among those who consumed >4 bottles/week. Further previous studies reported the association of diet soda and artificial sweeteners with a high body mass index and cardiometabolic consequences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reverse holds for non-caloric flavor consumption (associated with obesity only). Our findings are in line with a previous study conducted among 609 patients with diabetes 14 and found a two-fold increase in proliferative DR among those who consumed >4 bottles/week. Further previous studies reported the association of diet soda and artificial sweeteners with a high body mass index and cardiometabolic consequences.…”
Section: Discussionsupporting
confidence: 93%
“…Soft drink consumption: depend on validity and reproducibility of a 145-item self-administered food frequency questionnaire (FFQ), and according to it all patients sample were asked about consumption of soft drink then divided to no consumption when using less than 1 can/week (375mL), moderate when using 1–4 cans/week, severe when using more than 5 cans/week. 13 , 14 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, a meta-analyses of 11 cohorts reported that after adjustment for age, gender, energy intake, BMI, and other dietary covariates, each additional serving of sugar-sweetened beverage was associated with higher fasting glucose ( β ± SE 0.014±0.004 [mmol/L]; P =1.5×10 –3 ) and higher fasting insulin (0.030±0.005 [log e pmol/L]; P =2.0×10 –10 ) 30. Furthermore, literature on the consumption of fizzy drinks reports that they increase the risk of diabetic complications, ie, chronic kidney disease and proliferative diabetic retinopathy 31,32…”
Section: Discussionmentioning
confidence: 99%
“…The growing popularity of diet soft drinks in recent years has been driven by increasing recognition of the adverse health consequences of sugar consumption and, in particular, the potential harms of sugar-sweetened soft drinks. 4 The cross-sectional study of 609 people with diabetes (87.5% type 2 diabetes) investigated the association between soft drink consumption and diabetic retinopathy (DR). 'Regret nothing no sugar, no calories' is a recent marketing catchphrase of a leading diet soft drink.…”
mentioning
confidence: 99%
“…2,3 An interesting study by Fenwick et al, in this edition of the Journal, highlights the potential harm of diet soft drink consumption in people with diabetes. 4 The cross-sectional study of 609 people with diabetes (87.5% type 2 diabetes) investigated the association between soft drink consumption and diabetic retinopathy (DR). Individuals who consumed more than four cans of diet soft drink per week (heavy consumption) had more than a two-fold increased likelihood of having proliferative DR (OR = 2.62) than those who did not.…”
mentioning
confidence: 99%